Measles Outbreaks in Afghanistan - Abubakr Yosufi; Hedayatullah Ehsan; Ali Maisam Eshraqi; Abdul Majeed Momeni (Pediatric Infectious Disease)
Afghanistan has been facing multiple measles outbreaks recently. As Afghanistan is currently witnessing a severe humanitarian crisis, controlling measles outbreaks has become very challenging due to the country's nearly collapsed health infrastructure. Even though there have been years of efforts to eliminate measles such as measles vaccination and campaigns, multiple outbreaks and dozens of fatalities are reported every year. Lately a widespread measles vaccination campaign was held in 2022, but still, thousands of measles cases were reported afterwards. Severe widespread poverty, decades of civil unrest, armed conflict, and recently coronavirus disease 2019 (COVID-19) pandemic, and lack of funding have been a huge obstacle to curb the disease. To eliminate the disease and prevent its spread to measles-free countries through migration, Afghanistan needs immediate global support. Purpose: This paper aims to comment on the measles outbreak challenges amid the current severe humanitarian crisis in Afghanistan, along with recommendations to overcome the persistent outbreaks.